2000
DOI: 10.1016/s0002-9440(10)64706-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation by Size of Epithelial Tumor Cells

Abstract: We have developed a new assay, ISET (isolation by size of epithelial tumor cells), which allows the counting and the immunomorphological and molecular characterization of circulating tumor cells in patients with carcinoma, using peripheral blood sample volumes as small as 1 ml. Using this assay, epithelial tumor cells can be isolated individually by filtration because of their larger size when compared to peripheral blood leukocytes. ISET parameters were defined using peripheral blood spiked with tumor cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
519
2
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 957 publications
(535 citation statements)
references
References 16 publications
6
519
2
3
Order By: Relevance
“…As EpCAM and cytokeratin are not expressed in a fair proportion of CTCs, this method has had to be continuously improved. Isolation by size of epithelial tumor cells (ISET) allows highly sensitive enrichment, morphological identification, and enumeration of CTCs (Vona et al, 2000). In one study based on the ISET method, CTCs were found in 18 of 29 patients (62.0%) with primary invasive melanoma and in five out of eight patients (62.5%) with metastatic melanoma (De Giorgi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…As EpCAM and cytokeratin are not expressed in a fair proportion of CTCs, this method has had to be continuously improved. Isolation by size of epithelial tumor cells (ISET) allows highly sensitive enrichment, morphological identification, and enumeration of CTCs (Vona et al, 2000). In one study based on the ISET method, CTCs were found in 18 of 29 patients (62.0%) with primary invasive melanoma and in five out of eight patients (62.5%) with metastatic melanoma (De Giorgi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…8) On the other hand, it has been reported that non-adherent abnormal CTCs can be detected based on the expression of tumor antigens and biophysical deformities. 9,[11][12][13][14][15][16][17][18] The positive expression of CTC protein markers such as cytokeratin -8, -18 and -19, CD44 and the epithelial cell adhesion molecule (EpCAM) is often found in a CTC. 10) To date, the CellSearch system (Veridex, LLC, USA), which is based on immunostaining for CKs + , CD45 -and nucleus + , is the only device that is currently approved by the Food and Drug Administration for CTC detection,.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 CTCs are rare cells present in the blood in numbers as low as one CTC per 10 6 -10 7 leukocytes, which makes their capture and detection very challenging. The techniques currently used for CTC capture include immunomagnetic separation, 6,8 membrane filters, 11,12 and micro-electro-mechanical system (MEMS) chips. 13,14 All of these techniques are subject to limitations.…”
mentioning
confidence: 99%